Complete replacement of corn by white or red sorghum in japanese quail feeds - Freitas,ER (2014)
This study aimed at evaluating the total replacement of corn by white or red sorghum and the inclusion or not of pigment in the diet on the performance and yolk color of Japanese quail eggs. In the trial, 210 Japanese quails were distributed according to a completely randomized experimental design consisting of five treatments with six replicates of seven birds each. Treatments consisted of Corn-based diet (C), white sorghum-based diet (WS), white sorghum-based diet + pigment (WSP), red sorghum-based diet (RS), and red sorghum-based diet + pigment (RSP). Feed intake, feed conversion ratio, egg production, and egg mass were no influenced by the treatments. However, paler egg yolks were produced when corn was replaced by sorghum. When red and white sorghum varieties were compared, there were no differences in yolk color or response to pigment dietary inclusion. It was concluded that the total replacement of corn by sorghum in the feed did not influence the performance of Japanese quails and that yolk color response is not affected by the inclusion of pigments in diets containing sorghum, independently of its variety.